Distributed Cross‐Domain Link Creation for Flexible Data Integration and Manageable Data Interoperability Standards. Issue 1 (12th April 2022) - Reichwein, Axel
ABSTRACT: A distributed link creation strategy represents a shift from the traditional centralized link creation strategy used for data integration. A distributed link creation strategy provides a more flexible, user‐friendly approach for engineers to specify cross‐domain links between different domains of engineering data, which is key to achieving traceability across different product lifecycle phases. A new type of API that allows API clients to find link targets easily and create links makes this possible. Features of this new link‐enabling API include support for the open‐world assumption, embeddable search dialogs, and hypermedia for self‐discovery. Furthermore, a distributed link creation strategy also supports more efficient standardization efforts to achieve data interoperability by only requiring small, thus more manageable, domain‐specific standards in combination with standardized cross‐domain links, in contrast to the typically large, therefore unmanageable, multi‐domain standards.